Low-cost locally manufacturable unilateral imperial external fixator for low- and middle-income countries - Saeidi, Mehdi; Barnes, Spencer C.; Berthaume, Michael A.; Holthof, Sander R.; Milandri, Giovanni S.; Bull, Anthony M. J.; Jeffers, Jonathan (Frontiers in Medical Technology, 2022)
Treating open fractures in long bones can be challenging and if not performed properly can lead to poor outcomes such as mal/non-union, deformity, and amputation. One of the most common methods of treating these fracture types is temporary external fixation followed by definitive fixation. The shortage of high-quality affordable external fixators is a long-recognised need, particularly in Low- and Middle-Income Countries (LMICs). This research aimed to develop a low-cost device that can be manufactured locally to international standards. This can provide surge capacity for conflict zones or in response to unpredictable incidents and situations. The fixator presented here and developed by us, the Imperial external fixator, was tested on femur and tibia specimens under 100 cycles of 100 N compression-tension and the results were compared with those of the Stryker Hoffmann 3 frame. The Imperial device was stiffer than the Stryker Hoffmann 3 with a lower median interfragmentary motion (of 0.94 mm vs 1.48 mm). The low-cost, easy to use, relatively lightweight, and easy to manufacture (since minimum skillset and basic workshop equipment and materials are needed) device can address a critical shortage and need in LMICs particularly in conflict-affected regions with unpredictable demand and supply. The device is currently being piloted in three countries for road traffic accidents, gunshot wounds and other conflict trauma – including blast cohorts.